Examination of Acceleration and Speed Performances According to Different Foot Sole Sizes in Sedentary Women - Cengiz Taşkin,; Ali Kemal Taşkin, (Journal of Educational Issues, 2024)
In this study, it was aimed to examine the acceleration and speed performances of sedentary women according to their different foot sole length. 60 women that recide in Gaziantep and live sedentary life has participated voluntarily. The subjects were divided into 4 groups in terms of foot sole length and metatarsus width. The average age of the subjects that are participated in the study is determined as 15.8±0.76 for the 1st group, 16.1±1.13 for the 2nd group, 15.9±1.12 for the 3rd group and 15.7±1.33 for the 4th group. Foot sole, metatarsus measurements, acceleration and speed performance values of the subjects were taken in accordance with the measurement technique. All data that is obtained in the study were compared with each other and analyzed in terms of groups while using the SPSS 20.0 software package. When we evaluate the results of the analysis; it can be seen that there are significant differences that is detected between the 1st, 3rd and 4th groups in terms of acceleration performance in terms of foot sole length and metatarsus width; however, no significant difference was found between the 2nd group and the other groups. Although small differences were detected between the groups when it comes to sprint performance, these differences were not statistically significant. As a result, it was observed that there were differences between the groups in terms of acceleration performance, but there was no significant difference in terms of speed performance.